Enhanced passive safety surveillance of three marketed influenza vaccines in the UK and the Republic of Ireland during the 2017/18 season. Issue 9 (2nd September 2019) - Gandhi-Banga, Sonja; Chabanon, Anne-Laure; Eymin, Cecile; Caroe, Timothy; Butler, Karina; Moureau, Annick
ABSTRACT: Safety surveillance is required for each season's influenza vaccines to rapidly detect and evaluate potential new safety concerns before the peak period of immunization. Here we report the results of an enhanced passive safety surveillance for a trivalent split-virion inactivated influenza vaccine (IIV3; Vaxigrip®), an intradermal version of this vaccine (IIV3-ID; Intanza® 15 µg), and a recently licensed quadrivalent version (IIV4; VaxigripTetra TM ) during the 2017/18 influenza season in the UK and Republic of Ireland. The primary objective was to determine the rates of adverse reactions (ARs) occurring within 7 days following routine vaccination. Between September and November 2017, 979 safety report cards were distributed to vaccinees receiving IIV3-ID, 1005 to those receiving IIV3, and 957 to those receiving IIV4. At least one AR was reported by 28 participants (2.9%) vaccinated with IIV3-ID, 14 participants (1.4%) vaccinated with IIV3, and 20 participants (2.1%) vaccinated with IIV4. The most frequent ARs were injection-site reactions and headache. One participant vaccinated with IIV3-ID reported two suspected serious ARs (dyskinesia and a shock symptom), although these could not be confirmed as vaccine-related. Rates of ARs for IIV3 and IIV3-ID for 2017/18 did not differ from the 2016/17 rates. For IIV4, in its first season since licensure, AR frequencies were similar to those in the Summary of Product Characteristics. In conclusion, no change was found compared to the known or expected AR rates for IIV3, IIV3-ID, or IIV4 during the 2017/18 season.